Study on a Novel Water-Soluble Hydrophobically Associating Polymer as an Enhanced Heavy Oil Recovery Agent. (3rd November 2021) - Qiao, Dongyu; Ye, Zhongbin; Wang, Xindong; Zheng, Yiping; Tang, Lei; Lai, Nanjun
Abstract : In this study, emulsion-free radical reaction was applied to synthesize a novel sulfomethylating hydrophobically associating copolymer (HPDS) by using acrylamide, acrylic acid, NaHSO3, HCHO, and a laboratory-made N, N-divinylnonadeca-1, 10-dien-2-amine to enhance heavy-oil recovery. The structure and properties of HPDS were characterized by a range of experiments, which showed that HPDS had better stability and enhanced heavy-oil recovery capacity than hydrolyzed polyacrylamide (HPAM). One-dimensional flooding experiments illustrated that HPDS performed better in establishing resistance factor (RF) and residual RF (RRF), and approximately 19.8% oil recovery could be enhanced by injecting 1500 mg/L of HPDS solution compared with that of HPAM at only 14.1%. HPDS has a promising application prospect in enhancing heavy-oil recovery.